In peace prepared : innovation and adaptation in Canada's Cold War army - Godefroy, Andrew B., 1972- (Studies in Canadian military history., 2014)
Although the Allies claimed victory at the end of the Second World War, the United States' invention of the atomic bomb and its replication by the Soviet Union posed new dangers for all nations. This book examines what Canada's Cold War Army did to prepare for war against the Warsaw Pact armies -- and why and how it did it.--Publisher's description.